Exploring the potentials and impact of indigenous Ghanaian dishes in the restaurant sector within the hospitality industry / Akua Serwah, Derweanna Bah Simpong and Marlisa Abdul Rahim - Serwah, Akua; Simpong, Derweanna Bah; Abdul Rahim, Marlisa (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The Ghanaian hospitality industry is far from fully exploring the potential of indigenous cuisines to spur the industry's growth. Therefore, the purpose of this paper is to formulate a new model and assess the performance of indigenous Ghanaian dishes in the hospitality industry based on the Knowledge, Attitude and Practice (KAP) model. The paper focuses on exploring Ghanaian indigenous cuisine's potential, factors affecting the promotion and moderating role of advertisement and location. The explanatory method involved the survey of chefs, cooks, waiters, waitresses and managers sampled through multiple methods. Data collected through a structured questionnaire was analyzed using descriptive and inferential statistical methods. The inferential statistical methods included confirmatory factor analysis (CFA), correlational analysis, and structural equation modelling (SEM). The study contributes to existing knowledge by coming out with a new model that has the potential to improve the contributions of indigenous dishes to the hospitality industry of Ghana.